The significance of DNA mismatch repair (MMR) in breast cancer - Romanowicz, Hanna; Smolarz, Beata; Fiks, Tomasz; Kulig, Andrzej; Połać, Ireneusz; Sobczuk, Anna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2010)
Background: Microsatellite instability (MSI) is due to defective DNA mismatch repair. Defects in DNA mismatch-repair (MMR) genes lead to replication errors revealed as instability in microsatellite markers. Studies have shown that breast cancer may be associated with mutations in mismatch repair genes, such as MSH2, MSH3, MSH4, MSH6, MLH1, MLH3, PMS1 and MUTYH. Aim: Results from studies that assayed MMR in sporadic breast cancer are reviewed. Conclusion: Several data suggest that microsatellite instability seems to be a risk factor for breast cancer in subjects belonging to HNPCC (hereditary non-polyposis colorectal cancer) families with high incidence of this cancer and sporadic breast cancer.